(untitled) (Journal of Engineering, 2025)
An experimental analysis was conducted to investigate the effect of varying the inlet airflow rate into the drying chamber on the performance of an indirect solar dryer using a forced convection system under the climatic conditions of Baghdad, Iraq, at a latitude of 33.3°N. The dryer performance was tested at three airflow rates (0.0113, 0.0169, and 0.0226) m³/s, using a conventional flat absorber plate and a perforated plate with circular holes of diameter 3 mm. Apricots were dried in all experiments conducted in June 2024. The results showed that the perforated plate significantly enhanced the thermal efficiency of the solar collector compared with that of the flat plate. The perforated plate improved the heat exchange by disturbing the thermal boundary layer and improving airflow. The results also indicated that a low airflow rate (0.0113 m³/s) achieved the best drying efficiency, reducing the apricot moisture content from 80% to 42% for the perforated plate and 47% for the flat plate within 8 h, with maximum drying efficiencies of 28.44% and 22.22%, respectively. Although a higher airflow rate (0.0226 m³/s) improved the thermal efficiency of the collector, it was less effective for enhancing the drying process. The results of this study demonstrated that operating an indirect solar dryer with a perforated absorbent plate at a low airflow rate accelerates the removal of moisture from the product while maintaining its quality. This makes the system suitable for practical agricultural applications in hot and dry environments, where drying speed and efficiency are critical for reducing postharvest losses and increasing product storage life.